Prolonged acidosis is a feature of SGLT2i-induced euglycaemic diabetic ketoacidosis. (27th September 2019) - Rafey, Mohammed Faraz; Butt, Arslan; Coffey, Barry; Reddington, Lisa; Devitt, Aiden; Lappin, David; Finucane, Francis M
Abstract : Summary: We describe two cases of SGLT2i-induced euglycaemic diabetic ketoacidosis, which took longer than we anticipated to treat despite initiation of our DKA protocol. Both patients had an unequivocal diagnosis of type 2 diabetes, had poor glycaemic control with a history of metformin intolerance and presented with relatively vague symptoms post-operatively. Neither patient had stopped their SGLT2i pre-operatively, but ought to have by current treatment guidelines. Learning points: SGLT2i-induced EDKA is a more protracted and prolonged metabolic derangement and takes approximately twice as long to treat as hyperglycaemic ketoacidosis. Surgical patients ought to stop SGLT2i medications routinely pre-operatively and only resume them after they have made a full recovery from the operation. While the mechanistic basis for EDKA remains unclear, our observation of marked ketonuria in both patients suggests that impaired ketone excretion may not be the predominant metabolic lesion in every case. Measurement of insulin, C-Peptide, blood and urine ketones as well as glucagon and renal function at the time of initial presentation with EDKA may help to establish why this problem occurs in specific patients.